Hex mesh topological improvement based on frame field and sheet adjustment. (October 2018) - Wang, Rui; Gao, Shuming; Zheng, Zhihao; Chen, Jinming
Abstract: High-quality hex meshes are crucial for finite element analysis. However, geometric smoothing techniques applied for improving the quality of a hex mesh cannot ensure that the requirements of finite element analysis are satisfied. Therefore, to address this challenge, in this paper, we present a novel approach for topological optimization of a hex mesh based on frame field and sheet adjustment. Our approach improves the quality of the worst elements of the hex mesh by optimizing its topological structure. The approach first builds an initial frame field from the input hex mesh and then optimizes it to obtain a resultant high-quality frame field. Next, according to the initial and optimized frame fields, the process determines the most problematic sheet that degrades the quality of the hex mesh. Finally, based on the high-quality frame field and the current topological structure of the hex mesh, our approach uses sheet operations to adjust the structure of this most problematic sheet. Experimental results demonstrate that our topological optimization approach can effectively improve the minimum Scaled Jacobian value of the hex mesh. Highlights: Optimized frame field and sheet adjustment are applied to hex mesh topological improvement. The quality of the worst elements of the hex mesh is improved. The most problematic sheet is determined with the lowest structure quality among the related sheets to worst elements. The sheet adjustment is performed by problematic sheet redirection guided by high-quality frame field.